2020
DOI: 10.4149/gpb_2020022
|View full text |Cite
|
Sign up to set email alerts
|

The TrkB agonist 7,8-dihydroxyflavone improves sensory-motor performance and reduces lipid peroxidation in old mice

Abstract: 7,8-Dihydroxyflavone (7,8-DHF) is a natural flavonoid compound that act as Trk-B agonist. 7,8-DHF is also a potent antioxidant. When applied systematically, 7,8-DHF can pass through bloodbrain barrier and exhibit potential therapeutic effects in several animal models of neurodegenerative disorders. This study investigates the remedial effects of 7,8-DHF on behavioral impairments and biochemical changes associated with aging with a species emphasis on cortex. For this purpose three experimental groups were form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Based on present results, we concluded that administration of 7,8-DHF alleviates hepatic and renal oxidative stress in some degree, as well as nitric oxide depletion in liver, kidney and heart tissues. While previous studies have shown that 7,8-DHF presents anti-aging properties on dermal fibroblast cells [34], reduces memory loss by inhibiting agerelated changes in hippocampal cells [7], and reduces lipid peroxidation in cerebral cortex and improves sensory motor performance in aged mice [8] for the first time in this study, we demonstrated that 7,8-DHF exihibited favorable effects on age related oxidative stress and/or NO depletion in non-neural tissues. However, as a major shortcoming of our study, the presence of oxidative stress and how it was affected by 7,8-DHF treatment should be supported by other classical parameters such as protein oxidation and antioxidant enzyme activities.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…Based on present results, we concluded that administration of 7,8-DHF alleviates hepatic and renal oxidative stress in some degree, as well as nitric oxide depletion in liver, kidney and heart tissues. While previous studies have shown that 7,8-DHF presents anti-aging properties on dermal fibroblast cells [34], reduces memory loss by inhibiting agerelated changes in hippocampal cells [7], and reduces lipid peroxidation in cerebral cortex and improves sensory motor performance in aged mice [8] for the first time in this study, we demonstrated that 7,8-DHF exihibited favorable effects on age related oxidative stress and/or NO depletion in non-neural tissues. However, as a major shortcoming of our study, the presence of oxidative stress and how it was affected by 7,8-DHF treatment should be supported by other classical parameters such as protein oxidation and antioxidant enzyme activities.…”
Section: Discussionmentioning
confidence: 44%
“…Using TrkB receptor agonist 7,8-dihydroxyflavone (DHF), Zeng et al [7] observed that age-related memory impairment and synaptic plasticity relieved in aged rats. In our previous study, we showed that 7,8-DHF improved sensory motor performance and reduced lipid peroxidation of brain cortex in aged mice [8].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Hang wire test was used to evaluate the grip strength, balance and endurance of mice [ 16 , 17 ]. As detailed in our previous study [ 18 ], the mouse was placed on a stretched wire with a thickness of 0.2 cm. The mouse had to support its body weight with its forelimbs.…”
Section: Methodsmentioning
confidence: 99%
“…The time of the first touch to the adhesive and time of removal of the adhesive reflect sensorimotor performance [ 19 , 20 ]. As previously described [ 18 ], a 3 × 3 mm square, red adhesive tape strips were stuck to the front paws of the mice. The time to touch one of the tapes with their nose or mouth and the time to remove each tape were used for statistical comparisons.…”
Section: Methodsmentioning
confidence: 99%